Climate and security revisited : Germany's priorities for the 2019/2020 UN Security Council period - Dröge, Susanne (2018)
Zusammenfassung: Germany will hold a non-permanent seat on the UN Security Council in 2019 and 2020, and has announced that climate fragility will be one of its priorities. However, the Council members’ interest in climate change and willingness to debate improving preparation for its security implications are very mixed. In continuing the follow-up to the Swedish-led debate of July 2018, Germany will face three challenges. First, adding value for all parties involved, the vulnerable developing countries as well as the permanent five countries in the Security Council. Second, matching ambitions with resources; in particular, Germany’s credibility as a climate policy leader needs to be maintained and engagement needs to be pushed at the highest level possible. Third, managing expectations on possible Security Council progress on this non-traditional security issue in the next two years. Diplomatic efforts should improve information flows for countries suffering from climate change impacts, intensify connections across forums inside and outside the UN, and lay out what can actually be achieved through the Security Council